Acupuncture and related therapies for anxiety and depression in patients with premature ovarian insufficiency and diminished ovarian reserve: a systematic review and meta-analysis - Huang, Sidan; Zhang, Danni; Shi, Xuliang; Zhang, Yi; Wang, Xuesong; She, Yanfen; Liang, Ce; Li, Xinyue; Zaslawski, Christopher (Frontiers in Psychiatry, 2024)
BackgroundThe decreased ovarian function has a negative impact on the mental health of women and increases the risk of anxiety and depression. A growing number of clinical studies have demonstrated that acupuncture-related therapies can effectively and safely restore hormone levels and improve ovarian reserve function. However, the effectiveness of acupuncture-related therapies in alleviating anxiety and depression symptoms in patients with ovarian hypofunction has not been thoroughly evaluated. Therefore, this study conducted a systematic review and meta-analysis to assess the impact of the different acupuncture-related therapies on the mental health of patients with ovarian hypofunction.MethodsWe comprehensively searched eight famous databases for randomized controlled trials up to October 30, 2024. Databases include PubMed, Web of Science, EMBASE and Cochrane Library, China Biomedical (CBM), China National Knowledge Infrastructure (CNKI), Wanfang Database and VIP Database.ResultsThe study included 12 RCTs, involving 780 patients with ovarian hypofunction, including 403 patients with POI, 297 patients with DOR, and 80 patients with POF. Acupuncture-related therapy was obviously superior to hormone therapy in relieving anxiety symptoms (SMD: -0.90; 95%CI: -1.28, -0.53; P<0.000 01) and depressive symptoms (SMD: -0.82; 95% CI: -1.25, -0.40; P=0.0001).ConclusionsAcupuncture-related therapy was more effective than hormone therapy in improving anxiety and depression symptoms in patients with ovarian hypofunction. This study supports the use of acupuncture-related therapies for women experiencing decreased ovarian function associated with mental health issues.Systematic review registrationhttps://www.crd.york.ac.uk/, identifier CRD42023488015.